Influence of Service Quality and "BSI Mobile Features" on Students Customer Satisfaction - Lestari, Vina Resti; Mujib, Haqibul; Aristhantia, Isti Tresna; Ahmadi, Riki (Syari'ah Economics, 2023)
This study aims to investigate the effect of BI mobile service quality and BSI mobile features on customer satisfaction among IAID Ciamis students using correlational quantitative research methods. The results showed that partially, service quality has a positive and significant effect on customer satisfaction (significance 0.017 <0.05, tcount> ttable (2.440> 1.989), and a positive regression coefficient of 0.271). BSI Mobile features also have a positive and significant effect on customer satisfaction (significance 0.000 <0.05, tcount> ttable (3.790> 1.989), and a positive regression coefficient of 0.981). At the same time, service quality and BSI Mobile features have a positive and significant effect on customer satisfaction (fhitung 40.463 > ftabel 3.09 and significance 0.000 <0.05). This study provides information about the relationship between variables, not about the causality between these variables.